2003
DOI: 10.1212/01.wnl.0000096014.90469.1c
|View full text |Cite
|
Sign up to set email alerts
|

Is there less micrographia in foreign language in Parkinson’s disease?

Abstract: Cerebral processing for native and foreign languages differs.1 A 71-year-old, right-handed Japanese man with a 5-year history of Parkinson disease (PD) noticed that micrographia was more severe in his written Japanese than his written English. The severity of PD was Hoehn & Yahr III, and Menesit 300 mg and Domin 0.8 mg were given daily. The patient was a retired priest who had been a high school English teacher until age 65. He had never lived in an English-speaking country and was not bilingual. He educated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…In literature, micrographia has been reported to be more frequent in native than secondary languages, owing to impaired execution of more utilized tasks 20. In our population, most subjects spoke only one language (English).…”
Section: Discussionmentioning
confidence: 71%
“…In literature, micrographia has been reported to be more frequent in native than secondary languages, owing to impaired execution of more utilized tasks 20. In our population, most subjects spoke only one language (English).…”
Section: Discussionmentioning
confidence: 71%
“…In line with the declarative/procedural model (Paradis, 1994(Paradis, , 2004Ullman, 2001Ullman, , 2004, the study showed that patients with PD are especially impaired in accessing implicit, procedural grammatical knowledge of L1. In a similar vein, a single case study (Yazawa, Kawasaki, & Ohi, 2003 ) reported a bilingual Japanese -English PD patient presenting a more severe micrographia in writing in his native language, which was likely more automatic, than in English writing. This evidence in PD suggest a greater involvement of the basal ganglia in the acquisition and further processing of L1, and in particular of L1 grammatical knowledge, thus further corroborating the view of a major involvement of procedural memory in representing L1 grammar (Paradis, 2004 ).…”
Section: Bilingualism and Progressive Neurodegenerative Disordersmentioning
confidence: 86%
“…Also, Yazawa, Kawasaki, and Ohi (2003) describe a bilingual Japanese-English patient whose micrographia (a common and well-known symptom of Parkinson's disease) was more severe in his written Japanese (his native language) than his written English (his second language). The patient had never lived in an English-speaking country and was not considered bilingual.…”
Section: Huntington's and Parkinson's Diseases In Bilingual Individualsmentioning
confidence: 99%